Letter to the Editor RE: Treatment of Gout and Hyperuricemia (April Vol 29, No2,2011 Page 85-95) - Das, Aparna (Journal of Bangladesh College of Physicians and Surgeons, 2012)
DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9443 JBCPS 2011; 29(3): 180-181